Level of appropriation of Stakeholders to the USR in a Colombian Public Accounting program - Reyes-Bastidas, Carolina; Villarreal, José Luis; Camargo-Mayorga, David Andrés (Universidad Pedagógica y Tecnológica de Colombia, 2024)
The objective of this article is to analyze the level of appropriation of internal stakeholders (students, teachers and managers) assigned to the Public Accounting Program of the Mariana University (Pasto, Colombia) to the dimensions of University Social Responsibility (USR). For this purpose, a sample of 121 students, 28 teachers and 2 managers (dean and director of the program) was used and three hypotheses were formulated from the review of the literature that were tested in two phases: the first exploratory, through factor analysis and, the second confirmatory, with the structural equation model. The main results show that the internal stakeholders of the Mariana University perceive that research with a social focus is related to the dimension of social projection, and that RSU with an educational focus is not related to research with a social focus, but it is related to the dimension of social projection.